Exposure to artificial light at night mediates the locomotion activity and oviposition capacity of Dastarcus helophoroides (Fairmaire) - Jiang, Xiang-lan; Ren, Zhe; Hai, Xiao-xia; Zhang, Ling; Wang, Zhi-gang; Lyu, Fei (Frontiers in Physiology, 2023)
Light entrains the endogenous circadian clocks of organisms to synchronize their behavioral and physiological rhythms with the natural photoperiod. The presence of artificial light at night disrupts these photoperiodic cues and is currently considered to be a major threat to key fitness-related behaviors, including sleep disruption and physiological stress. Research on the ecological influence of forest pest and their natural enemies is lacking. The wood-boring insects significantly damage forest and urban forest ecosystem functions. The parasitic beetles, Dastarcus helophoroides is an important natural enemy of wood-boring insects, especially those in the Cerambycidae family. However, the effect of artificial light at night on the locomotor rhythms and oviposition capacity of D. helophoroides has received little attention. To address this gap, diel changes in the locomotor activity and number of eggs laid by female D. helophoroides was analyzed under different light-dark (LD) cycles and temperatures. The results showed that the 24-h rhythmic of locomotor activity in these beetles was elevated in darkness and reduced under illumination, indicating that they are nocturnal insects. This activity has two major peaks, the evening (1-8 h after lights off) and morning (3.5-12.5 h after lights off) components, reflecting that light mediate regular changes in locomotor activity. Moreover, the circadian rhythms and active percentage were influenced by the illumination duration and temperature, especially constant light and 40 ℃. Females laid more eggs under the 16 L: 8 D cycles at 30 ℃ than under the other combinations of photoperiod (including constant light and darkness) and temperature. Finally, the potential influence of exposure to four ecologically relevant intensities of artificial light at night (0, 1, 10 or 100 lx) on oviposition capacity was studied. The results showed that lifetime exposure to bright artificial light (1-100 lx) at night decreased the number of eggs laid relative to those laid with no lighting at night. These results demonstrate that chronic exposure to bright artificial light at night may influence the locomotor activity and oviposition capacity of this parasitic beetle.